Imagining Death in Spenser and Milton
XI, 216 p. 7 illus.
Keywords: Imagining Death in Spenser and Milton assembles a collection of essays on the compelling topic of death in two monumental representatives of the early modern canon, Edmund Spenser and John Milton. The volume draws its impetus from the conviction that death is a central, yet curiously understudied, preoccupation for Spenser and Milton, contending that death - in all its early modern reformations and deformations - is an indispensable backdrop for any attempt to articulate the relationship between Spenser and Milton.